DAMPAK PEMBANGUNAN RUANG TERBUKA HIJAU KASUS TAMAN CAHAYA KOTA SURABAYA - Endik Hidayat; Efrem Suryatno Partama (Prodi Ilmu Politik, 2021)
This study aims to find out how the impact of the green open space development policy in the city of Surabaya, especially in the Cahaya park, Babat Jerawat sub-district, Pakal district, Surabaya. This research use desciptive qualitative approach. Data collection techniques through in-depth interviews, observation, and documentation. Data analysis in this study starts from the process of collecting data, reducing data, displaying data and drawing conclusions. To find out the impact felt by the community around Pakal District with the construction of the Cahaya park, researchers used the policy impact dimensions proposed by Thomas R. Dye, there are two main findings. First, the Cahaya Park was built in the Babat Jerawat sub-district, Pakal sub-district, Surabaya, the purpose of the Cahaya park was to overcome the problems that exist in the community, especially the need for recreation areas, sports facilities, and children's playgrounds. Second, the park which was originally opened was the target of the policy as a place of recreation and as a biofilter against air conditions polluted by pollution, besides that there are groups outside the policy target, namely the community in Babat Jerawat Village, Pakal District, who also use the park for selling activities so that some people who used to be unemployed with the opening of the Cahaya park they can have a job as a merchant times five